2020
DOI: 10.1111/1750-3841.15035
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activities of mamao luang (Antidesma thwaitesianum Müll. Arg.) fruit: Extraction and application in raw chicken patties

Abstract: Extraction of mamao luang (hereafter called mamao) with different solvents and varying solid to liquid (S:L) ratio was conducted to verify its antioxidant activities. Total phenolic content (TPC), total flavonoid content, total monomeric anthocyanin content, and antioxidant activities, namely, 2,2‐diphenyl‐1‐picrylhydrazyl (DPPH) free radical scavenging activity and ferric reducing antioxidant power (FRAP) of the unrefined extracts, were analyzed. The extraction with 70% acetone and 70% methanol and the S:L ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 41 publications
4
5
0
Order By: Relevance
“…The inhibitory effects of spice extracts on TBARS formation were as followed: Cloves ≈ allspice ≈ black seed ≥ nutmeg ≈ caraway ≈ bay leaf > cardamom > control. Our findings confirmed the results of other authors who had added various plant extracts and thereby inhibited the development of lipid oxidation in chicken raw meat [9,[11][12][13]29,36,41].…”
Section: Tbarssupporting
confidence: 92%
See 4 more Smart Citations
“…The inhibitory effects of spice extracts on TBARS formation were as followed: Cloves ≈ allspice ≈ black seed ≥ nutmeg ≈ caraway ≈ bay leaf > cardamom > control. Our findings confirmed the results of other authors who had added various plant extracts and thereby inhibited the development of lipid oxidation in chicken raw meat [9,[11][12][13]29,36,41].…”
Section: Tbarssupporting
confidence: 92%
“…The CD concentrations of the samples increased with time, reaching the highest values on the 12th day of storage at 4 • C, apart from the sample with nutmeg for which the maximum CD content was observed after 10 days ( Figure 1). The results are in agreement with [36], as an increase of CD concentration of the raw chicken patties with mamao luang fruit was observed during 12 days of storage at 4 • C and also [13], reported an increase of CDs during chilled storage of raw ground pork samples. Others indicated that the CD content of the control sample of raw chicken patties was picked on 7th day of storage and dropped thereafter [36] and that the maximum CD concentration in the control sample of cooked chicken thigh was observed on the 2nd day of 5 days of chilled storage [37].…”
Section: Content Of Cdssupporting
confidence: 89%
See 3 more Smart Citations